Les chanteuses à la barre - Mélanie Traversier (Criminocorpus)
In the 18th century, Naples is considered as the uncontested capital of opera. Singing for opere buffe or opere serie, the female opera singers hired by the Neapolitan public theatres play an important role in promoting the musical prestige of the city. However a social stigmat is still attaches to them: in the best way they are described as capricious, in the worst they are viewed as scandalous temptresses threatening the social order. The archives of the competent court for public performances and their professionals reflect this ambivalence. The judicial documentation that have been neglected in the past by the historians of opera reveals the internal professional tensions inside the “showbiz society”, involving female and male singers against the theatres directors. But it also illustrates the complex relations between the female singers and their male concurrents on the operatic stage, and between them and their companions or protectors. These conflicts exposed on court help to understand the singularity of the female singers’ career, their progressive professionalization, and beyond the difficult and slow redefinition of their image in the social representations. On this basis, this article falls within the conjunction of a dual recent historiographical renewal considering the performing arts: on the one hand, the history of the relationships between law, legal practices and drama; on the other hand, the history of opera and vocal performances revisited by the gender studies.